2006
DOI: 10.1111/j.1468-1331.2006.01398.x
|View full text |Cite
|
Sign up to set email alerts
|

EFNS guideline on the treatment of cerebral venous and sinus thrombosis

Abstract: Cerebral venous and sinus thrombosis (CVST) is a rather rare disease which accounts for <1% of all strokes. Diagnosis is still frequently overlooked or delayed due to the wide spectrum of clinical symptoms and the often subacute or lingering onset. Current therapeutic measures which are used in clinical practice include the use of anticoagulants such as dose-adjusted intravenous heparin or body weight-adjusted subcutaneous low-molecular-weight heparin (LMWH), the use of thrombolysis, and symptomatic therapy in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
193
0
19

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 259 publications
(215 citation statements)
references
References 30 publications
3
193
0
19
Order By: Relevance
“…Box 1 outlines some of the differential diagnoses we considered for our patient. [1][2][3][4][5][6] Headache, which occurs in 90% of patients, 1 is frequently severe and diffuse in nature and often precedes the onset of neurologic symptoms. 5 Behavioural symptoms, such as delirium, amnesia and mutism, can occur if the deep venous system is involved.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Box 1 outlines some of the differential diagnoses we considered for our patient. [1][2][3][4][5][6] Headache, which occurs in 90% of patients, 1 is frequently severe and diffuse in nature and often precedes the onset of neurologic symptoms. 5 Behavioural symptoms, such as delirium, amnesia and mutism, can occur if the deep venous system is involved.…”
Section: Discussionmentioning
confidence: 99%
“…7 Focal or generalized seizure, central motor deficits, sensory deficits, aphasia or hemianopia develops in 40%-60% of patients. 6 A multicentre prospective observational study involving more than 600 patients reported that 39.3% had seizures at presentation. 8 Alternating focal deficits are rare but characteristic of cerebral venous sinus thrombosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to the American and European Guidelines, the use of anticoagulants should be restricted to special cases, such as cerebral venous sinus thrombosis and possibly arterial dissections (2,13,19,20,54,62,66). Several studies have shown no benefit of anticoagulation in acute ischemic stroke (1,3,11,12,67).…”
Section: Other Treatmentsmentioning
confidence: 99%